Factores asociados con la incidencia de dengue: Revisión sistemática - Ruales Tapia, Juan Andrés (2024)
Dengue is an infectious febrile disease of systemic etiology, transmitted by the infected mosquito of the genus Aedes aegypti. Its main risk factors are visiting a geographical region with the presence of the vector and drinking water supply problems. This disease has increased drastically in recent decades worldwide, it is estimated that 50 millions of cases of dengue annually worldwide. The objective of this work was to determine the factors associated with the incidence of dengue in South America during the period 2000-2022. The applied methodology included the design of a bibliographic and descriptive study, working with a sample of 87 medical scientific articles, and published in the digital journals Google Scholar, Pubmed and Medline. The 87 selected papers met the previously established inclusion and exclusion criteria. The results revealed that socio-demographic and environmental factors have a greater incidence in dengue, while its prevalence is high in South America with an increase from 2000 to 2022 in coastal areas as well as in the low-income population, for its control preventive measures are applied as fumigation of homes, disposal of breeding sites and elimination of water stored in tanks, jars or tires, It has also been found that microbiology is being used for the eradication and control of the mosquito carrier, in view of this, it is concluded that this disease represents a risk to the population of South America, being advisable to strengthen the dissemination of its consequences to the community through the management of public and private health entities, as well as education on how to clean the possible reservoirs of the vector carrier